IMPLEMENTASI ENGLISH FOR SPECIFIC PURPOSES (ESP) MELALUI VIDEO EDUKASI BERBAHASA INGGRIS BERSTANDAR INTERNASIONAL DALAM MENINGKATKAN PEMAHAMAN MASYARAKAT TENTANG PERSALINAN AMAN - GINTING, SULASTRI BR; Br Ginting, Monika Nina; Tinambunan, Tedty Rohaya (INSTITUT KESEHATAN DELI HUSADA, 2026)
Public understanding of safe childbirth through the implementation of English for Specific Purposes (ESP) utilizing international-standard English educational videos in Kutalimbaru District, Deli Serdang Regency is motivated by the persistence of community perceptions and childbirth practices that do not yet fully align with health standards. The implementation methods included a preparation phase, identification of community needs, material delivery, educational video screenings, interactive discussions, mentoring, and evaluations via pre-tests and post-tests. The ESP approach was employed to introduce basic English terminology relevant to maternal health and childbirth contexts. The results of the activity indicate that the program was well-executed and received positive responses from the community. Participant attendance reached 85%, active participation was 78%, and the average score of participants increased from 56% in the pre-test to 84% in the post-test. Furthermore, 76% of participants were able to identify basic procedures for safe childbirth, and 82% stated that the educational videos improved their understanding of the material. This activity proves that the implementation of ESP through educational videos is effective in enhancing public health literacy regarding safe childbirth.